Environmental Education Strategies in Islamic Education to Create an Ecologically Minded Generation - Masnawati, Eli; Hariani, Mila; Mardikaningsih, Rahayu; Noviyanti, Derisma Vita; Safitri, Shinta Maulidia; Alfiyani HD, Ajeng; Saniatur, Asrida (Bulletin of Science, Technology and Society, 2023)
Islamic education has great potential to contribute to environmental conservation through the integration of Islamic values into environmental education. This research aims to analyze the gaps, challenges, and opportunities faced in such integration efforts. Using a qualitative method based on a literature study, this research explores environmental concepts in the Islamic perspective, such as “khalifah,” “mizan,” and the prohibition against “israf,” as well as their relevance to contemporary environmental issues. The results show that the current Islamic education system still faces various obstacles, including the lack of a relevant curriculum, limited competence of educators, and a lack of supporting infrastructure. Socio-cultural dynamics, such as low public awareness of environmental issues and a consumptive culture, are also significant obstacles. Nevertheless, there are great opportunities to strengthen environmental education in Islamic education through the use of educational technology, cooperation with environmental organizations, and adaptation to global frameworks, such as the Sustainable Development Goals (SDGs). This study concludes that the integration of environmental education in Islamic education requires a systematic and collaborative approach. By utilizing relevant Islamic values and support from various parties, Islamic education can be transformed into a strategic instrument to build a generation that has ecological awareness and responsibility for environmental conservation.